(untitled) (Homoeopathy for All, 2025)
Hypothyroidism is a widespread endocrine disorder characterized by an underactive thyroid gland, leading to various metabolic and physiological complications. This review explores the causes, symptoms, and diagnostic approaches for hypothyroidism, emphasizing both conventional and homeopathic treatment methods. Conventional management primarily involves levothyroxine therapy, while homeopathic treatments focus on personalized remedies such as Calcarea Carbonica, Lycopodium Clavatum, Sepia Officinalis, and Thyroidinum. While conventional treatment remains the gold standard, homeopathy serves as a complementary approach to symptom management. Future research should focus on optimizing individualized treatment strategies for improved patient outcomes.